Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
First, recall that \(\alpha\) and \(\beta\) are the roots of the quadratic equation \(x^2 + 5x + 6 = 0\). By Vieta's formulas, the sum and product of the roots for a quadratic equation \(ax^2 + bx + c = 0\) are given by:
[tex]\[ \alpha + \beta = -\frac{b}{a} \quad \text{and} \quad \alpha \beta = \frac{c}{a} \][/tex]
For our specific equation \(x^2 + 5x + 6 = 0\):
[tex]\[ a = 1, \, b = 5, \, c = 6 \][/tex]
Thus,
[tex]\[ \alpha + \beta = -\frac{5}{1} = -5 \][/tex]
[tex]\[ \alpha \beta = \frac{6}{1} = 6 \][/tex]
Now, we need to find \(\alpha^5 + \beta^5\). We can relate higher powers of \(\alpha\) and \(\beta\) using their lower powers. Using the identity:
[tex]\[ \alpha^5 + \beta^5 = (\alpha + \beta)(\alpha^4 + \beta^4) - \alpha \beta (\alpha^3 + \beta^3) \][/tex]
We need to express \(\alpha^4 + \beta^4\) and \(\alpha^3 + \beta^3\) in terms of \(\alpha + \beta\) and \(\alpha \beta\).
First, for \(\alpha^3 + \beta^3\), use the identity:
[tex]\[ \alpha^3 + \beta^3 = (\alpha + \beta)(\alpha^2 + \beta^2 - \alpha \beta) \][/tex]
To find \(\alpha^2 + \beta^2\), use the identity:
[tex]\[ \alpha^2 + \beta^2 = (\alpha + \beta)^2 - 2\alpha \beta \][/tex]
Substitute the known values:
[tex]\[ \alpha^2 + \beta^2 = (-5)^2 - 2 \cdot 6 = 25 - 12 = 13 \][/tex]
Thus,
[tex]\[ \alpha^3 + \beta^3 = (-5)(13 - 6) = -5 \cdot 7 = -35 \][/tex]
Next, for \(\alpha^4 + \beta^4\), use the identity:
[tex]\[ \alpha^4 + \beta^4 = (\alpha^2 + \beta^2)^2 - 2(\alpha \beta)^2 \][/tex]
Substitute the known values:
[tex]\[ \alpha^4 + \beta^4 = (13)^2 - 2 \cdot 6^2 = 169 - 2 \cdot 36 = 169 - 72 = 97 \][/tex]
Now, substitute everything back into the identity for \(\alpha^5 + \beta^5\):
[tex]\[ \alpha^5 + \beta^5 = (\alpha + \beta)(\alpha^4 + \beta^4) - \alpha \beta (\alpha^3 + \beta^3) \][/tex]
Substitute the known values:
[tex]\[ \alpha^5 + \beta^5 = (-5)(97) - 6(-35) \][/tex]
[tex]\[ \alpha^5 + \beta^5 = -485 + 210 = -275 \][/tex]
Therefore, the value of \(\alpha^5 + \beta^5\) is:
[tex]\[ \boxed{-275} \][/tex]
[tex]\[ \alpha + \beta = -\frac{b}{a} \quad \text{and} \quad \alpha \beta = \frac{c}{a} \][/tex]
For our specific equation \(x^2 + 5x + 6 = 0\):
[tex]\[ a = 1, \, b = 5, \, c = 6 \][/tex]
Thus,
[tex]\[ \alpha + \beta = -\frac{5}{1} = -5 \][/tex]
[tex]\[ \alpha \beta = \frac{6}{1} = 6 \][/tex]
Now, we need to find \(\alpha^5 + \beta^5\). We can relate higher powers of \(\alpha\) and \(\beta\) using their lower powers. Using the identity:
[tex]\[ \alpha^5 + \beta^5 = (\alpha + \beta)(\alpha^4 + \beta^4) - \alpha \beta (\alpha^3 + \beta^3) \][/tex]
We need to express \(\alpha^4 + \beta^4\) and \(\alpha^3 + \beta^3\) in terms of \(\alpha + \beta\) and \(\alpha \beta\).
First, for \(\alpha^3 + \beta^3\), use the identity:
[tex]\[ \alpha^3 + \beta^3 = (\alpha + \beta)(\alpha^2 + \beta^2 - \alpha \beta) \][/tex]
To find \(\alpha^2 + \beta^2\), use the identity:
[tex]\[ \alpha^2 + \beta^2 = (\alpha + \beta)^2 - 2\alpha \beta \][/tex]
Substitute the known values:
[tex]\[ \alpha^2 + \beta^2 = (-5)^2 - 2 \cdot 6 = 25 - 12 = 13 \][/tex]
Thus,
[tex]\[ \alpha^3 + \beta^3 = (-5)(13 - 6) = -5 \cdot 7 = -35 \][/tex]
Next, for \(\alpha^4 + \beta^4\), use the identity:
[tex]\[ \alpha^4 + \beta^4 = (\alpha^2 + \beta^2)^2 - 2(\alpha \beta)^2 \][/tex]
Substitute the known values:
[tex]\[ \alpha^4 + \beta^4 = (13)^2 - 2 \cdot 6^2 = 169 - 2 \cdot 36 = 169 - 72 = 97 \][/tex]
Now, substitute everything back into the identity for \(\alpha^5 + \beta^5\):
[tex]\[ \alpha^5 + \beta^5 = (\alpha + \beta)(\alpha^4 + \beta^4) - \alpha \beta (\alpha^3 + \beta^3) \][/tex]
Substitute the known values:
[tex]\[ \alpha^5 + \beta^5 = (-5)(97) - 6(-35) \][/tex]
[tex]\[ \alpha^5 + \beta^5 = -485 + 210 = -275 \][/tex]
Therefore, the value of \(\alpha^5 + \beta^5\) is:
[tex]\[ \boxed{-275} \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.